2018
DOI: 10.1111/dom.13197
|View full text |Cite
|
Sign up to set email alerts
|

Non‐severe hypoglycaemia is associated with weight gain in patients with type 1 diabetes: Results from the Diabetes Control and Complication Trial

Abstract: It is unclear whether the frequent non-severe episodes of hypoglycaemia observed during intensive glucose control in individuals with type 1 diabetes (T1D) are associated with subsequent weight gain. We analysed the association between non-severe hypoglycaemia and weight gain in 1441 Diabetes Control and Complication Trial (DCCT) participants. Non-severe hypoglycaemia was assessed by hypo-score (ie, number of blood glucose values <70 mg/dL divided by the total number of measurements during the DCCT quarterly v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
0
19
0
Order By: Relevance
“…The increase in food intake, associated with hypoglycemia treatment, can also have consequences on body weight. Recent data from DCCT study [30] have shown a significant association between non-severe hypoglycemia frequency and weight gain. In our study, we found 2.7 episodes of hypoglycemia a week, treated on average with 144.6 kcal.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…The increase in food intake, associated with hypoglycemia treatment, can also have consequences on body weight. Recent data from DCCT study [30] have shown a significant association between non-severe hypoglycemia frequency and weight gain. In our study, we found 2.7 episodes of hypoglycemia a week, treated on average with 144.6 kcal.…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…However, hypoglycemia, which still occurs daily in the majority of individuals with T1D, demands swift treatment with sugar-rich beverages such as soft drinks and/or ingestion of industrially processed food, often rich in fructose. As a consequence, weight gain due to hypoglycemia-induced defensive snacking is an important factor contributing to overweight or obesity ( Bumbu et al, 2018 ). Therefore, in individuals with T1D, especially when insulin therapy is not optimally tailored, weight gain due to energy- and fructose-rich defensive snacking could be a specific additional pathway leading to NAFLD susceptibility.…”
Section: Methodsmentioning
confidence: 99%
“…A proposed differential mechanism of liver damage in T1DM relates to the increase in visceral adiposity secondary to frequent snacking in the hypoglycemia context, which increases caloric and fructose intake [ 111 ]. Other mechanisms that may explain the development of hepatic complications in patients with T1DM are the relative portal vein insulin deficiency that leads to altered hepatic glycogen storage, absence of inhibition of hepatic gluconeogenesis, and overall metabolic disturbance with a shunt to lipogenic pathways [ 14 , 112 , 113 ].…”
Section: Diabetes Clinical Phenotypesmentioning
confidence: 99%